2013
DOI: 10.1021/jf402585t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Deliquescence Properties of Food Ingredients and Blends

Abstract: Deliquescence is a first-order phase transformation of a crystalline solid to a saturated solution that is triggered at a defined relative humidity (RH), RH0. Previous studies demonstrated that the RH0 of an inorganic substance with a positive heat of solution (ΔH) will decrease with increases in temperature. In this study, the relationships between ΔH, solubility, and deliquescence RH for single-ingredient and multicomponent systems were investigated. The deliquescence RHs of inorganic and organic crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 26 publications
(100 reference statements)
6
37
1
Order By: Relevance
“…This trend with temperature was expected since the heat of solution of T·2H 2 O is +20.7 ± 0.2 kJ/mol (Miller, de Pablo, & Corti, ), and according to the modified Clausius–Clapeyron equation in Lipasek et al. (), the RH 0 of a deliquescent compound with an endothermic heat of solution will decrease with increasing temperatures. The measured a w s of saturated T·2H 2 O solutions at 20, 25, 30, 35, and 40 °C (Figure ) were within 0.004 a w of the a w s of saturated trehalose solutions at the same temperatures reported in Galmarini, Chirife, Zamora, and Pérez ().…”
Section: Resultsmentioning
confidence: 70%
“…This trend with temperature was expected since the heat of solution of T·2H 2 O is +20.7 ± 0.2 kJ/mol (Miller, de Pablo, & Corti, ), and according to the modified Clausius–Clapeyron equation in Lipasek et al. (), the RH 0 of a deliquescent compound with an endothermic heat of solution will decrease with increasing temperatures. The measured a w s of saturated T·2H 2 O solutions at 20, 25, 30, 35, and 40 °C (Figure ) were within 0.004 a w of the a w s of saturated trehalose solutions at the same temperatures reported in Galmarini, Chirife, Zamora, and Pérez ().…”
Section: Resultsmentioning
confidence: 70%
“…Deliquescence describes the phase change of a crystalline solid to a saturated 26 solution droplet using water collected from the surrounding air. Temperature can affect the RH level 27 required to bring about deliquescence in hygroscopic substances but the effect varies between 28 compounds (Lipasek, et al, 2013). Temperature also has a significant influence over the saturation 29 vapour pressure of air (Lawrence, 2005) temperature influences the kinetics of drug dissolution only, rather than the thermodynamic 32 behaviour of solid particles, which remain relatively unchanged, and it is not expected to significantly 33 impact hygroscopic properties.…”
Section: Respiratory Drugs and Drug Delivery 22mentioning
confidence: 99%
“…Lipasek et al [27] reported that high temperatures tend to decompose the organic components in food. According to Bosca et al, [28] many products that are sensitive to heat may become degraded when subjected to high temperatures.…”
Section: Total Processing Timementioning
confidence: 99%